Titanium, workpieces and articles
Patent Information
- Application Number
- CN202580018675.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-05
- Filing Date
- 2025-02-28
- Publication Date
- 2026-09-29
AI Technical Summary
而且,原本钛材所具有的银白色的金属色会失去,因此在外观上有时不优选
[0032]根据本发明,能够得到提高润滑性并且具有本来的金属色的钛材、加工品和制品。
Smart Images

Figure CN122847552A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to titanium materials and their processed products, as well as articles containing them. Background Technology
[0002] Press forming is a method of shaping metal blanks by pressing them against a die and applying pressure. In press forming, adhesion between the blank and the die can sometimes become a problem. If adhesion occurs, lubrication deteriorates, reducing formability. Furthermore, surface defects may appear on the blank, or the die life may be shortened. Therefore, improving adhesion is required.
[0003] Industrial-grade pure titanium or titanium alloys (hereinafter referred to as "titanium materials") are prone to adhesion, meaning they have low lubricity. Therefore, when pressing titanium materials, a coating agent known as a film-type solid lubricant is usually applied to the surface. This improves lubricity and inhibits adhesion. However, using a film-type solid lubricant adds the steps of drying the surface after coating and cleaning the surface after pressing. As a result, manufacturing costs increase. Furthermore, lubricant residue tends to accumulate in the mold, reducing workability.
[0004] Given this, titanium materials with good lubricity that do not require the use of film-type solid lubricants have been developed. For example, Patent Document 1 discloses a titanium material whose lubricity is improved by forming a TiO2 coating. Furthermore, Patent Document 2 discloses a titanium material whose lubricity is improved by forming an oxide film or a nitride film on the surface.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-183551
[0008] Patent Document 2: Japanese Patent Application Publication No. 2005-298930
[0009] On the other hand, as disclosed in Patent Document 1, if a TiO2 coating that effectively improves lubricity is formed, the titanium material will acquire color due to light interference caused by the coating. Furthermore, the original silvery-white metallic color of the titanium material will be lost, which is sometimes undesirable in terms of appearance. Additionally, by forming the film to the point of losing its metallic color, there are concerns about changes in properties such as thermal conductivity, or difficulties in inspecting the appearance after forming. In the titanium material disclosed in Patent Document 2, the presence or absence of coloring was investigated, but from the viewpoint of maintaining the metallic color, there is room for further improvement. Summary of the Invention
[0010] The problem the invention aims to solve
[0011] In view of the above, the object of the present invention is to provide titanium materials, processed articles, and articles that improve lubricity and have their original metallic color.
[0012] Solution for solving the problem
[0013] The present invention was made to solve the above-mentioned problems, and its main purpose is to address the following titanium materials, processed articles and articles.
[0014] (1) A titanium material, wherein,
[0015] In the L*a*b* color system, the color difference ΔE*ab between the surface color (L*,a*,b*) of the titanium material and the reference color (L0*,a0*,b0*) expressed as in formula (i) below is 6.14 or less.
[0016] The nitrogen concentration Np, titanium concentration Tp, and carbon concentration Cp at the depth of the surface are measured by X-ray photoelectron spectroscopy. When the position with the highest nitrogen concentration is taken as the peak depth, the nitrogen concentration Np, titanium concentration Tp, and carbon concentration Cp at the peak depth satisfy the following equation (ii).
[0017]
[0018]
[0019] In formula (ii), Np, Tp, and Cp are represented by atomic percentages.
[0020] (2) The titanium material according to (1) above further satisfies the following formula (iii).
[0021]
[0022] (3) The titanium material according to (1) or (2) above further satisfies the following formula (iv).
[0023]
[0024] (4) A processed product, wherein,
[0025] In the L*a*b* color system, the color difference ΔE*ab between the color (L*,a*,b*) of at least a portion of the surface of the processed article and the reference color (L0*,a0*,b0*) expressed as in equation (i) below is 6.14 or less.
[0026] The nitrogen concentration Np, titanium concentration Tp, and carbon concentration Cp at the depth of the surface are measured by X-ray photoelectron spectroscopy. When the position with the highest nitrogen concentration is taken as the peak depth, the nitrogen concentration Np, titanium concentration Tp, and carbon concentration Cp at the peak depth satisfy the following equation (ii).
[0027]
[0028]
[0029] In formula (ii), Np, Tp, and Cp are represented by atomic percentages.
[0030] (5) An article comprising the titanium material described in any one of (1) to (3) above and / or the processed article described in (4) above.
[0031] The effects of the invention
[0032] According to the present invention, titanium materials, processed products, and articles with improved lubricity and their original metallic color can be obtained. Attached Figure Description
[0033] Figure 1 This is a graph showing the concentration distribution in the depth direction of an example of the titanium material in this embodiment. Detailed Implementation
[0034] In order to improve lubricity and maintain the original metallic color of titanium, the inventors conducted in-depth research and obtained the following insights.
[0035] Forming a coating on the surface of titanium (a) is an effective way to improve lubricity. On the other hand, to improve lubricity, a relatively thick coating is required. In this case, it becomes impossible to maintain the original metallic color of titanium. This is because if a thick coating is formed, it will exhibit different colors due to the interference of light.
[0036] (b) Therefore, the inventors investigated improving lubricity with a thin coating. Titanium typically forms a very thin passivation coating in the atmosphere. The passivation coating is composed of TiO2, but it peels off and breaks down during pressing, making it difficult to improve lubricity.
[0037] (c) The failure and peeling of the passivation coating are believed to occur due to the following mechanism: During pressing, compressive deformation and shear deformation caused by friction are applied to the base titanium material directly beneath the passivation coating. The passivation coating is very thin and has low ductility, so it is impossible to follow this deformation and form cracks on the passivation coating.
[0038] As forming progresses, the mold slides against the titanium material, forming abrasive powder containing both the passivation coating and the base titanium. This abrasive powder is transferred to the mold, further increasing friction. Moreover, shear deformation of the base titanium material directly beneath the passivation coating is promoted, increasing the crack density in the passivation coating and leading to its destruction and peeling. As a result, the easily adhered metallic titanium of the base material is eventually exposed.
[0039] (d) Therefore, the inventors investigated how hardening the base titanium material directly beneath the passivation coating can suppress shear deformation of the base titanium material in the portion directly in contact with the mold, thereby suppressing damage and peeling of the passivation coating. Furthermore, it was found that enriching N (nitrogen) directly beneath the passivation coating is effective, and that primary and secondary annealing under the conditions described later is effective in achieving N enrichment.
[0040] One embodiment of the present invention is based on the above insights. Hereinafter, the characteristics of the titanium material according to this embodiment will be described in detail.
[0041] 1. Composition of titanium materials
[0042] 1-1. Color difference
[0043] The titanium material of this embodiment has a passivation coating on its surface. This passivation coating needs to be set to a thickness that does not affect the original metallic color of the titanium material. Therefore, the titanium material of this embodiment has a passivation coating on its surface. * a * b * In the coloring system, the color of the titanium surface (L) * ,a * ,b * ) and the reference color (L0) represented by the following formula (i) * ,a0 * ,b0 * The color difference ΔE * The ab value is below 6.14.
[0044]
[0045] L * a * b * A colorimetric system refers to the colorimetric system specified in JIS Z 8781-4:2013, used to represent colors numerically. Furthermore, it can be based on L... * a * b * The corresponding values (luminance index and chromaticity index) are used to define each color. Here, the reference color mentioned above is the typical silvery-white color of titanium, which is (L... * ,a * ,b * ) is the (L0) of the above equation (i). * ,a0 * ,b0 * In the case of ), specifically, it is represented by the three values on the right-hand side of the above equation (i) (L) * ,a * ,b * (a specific color).
[0046] In addition, color difference ΔE * ab is an indicator representing the difference between two colors. In the case of this application, the color difference ΔE * The larger the ab value, the greater the color difference between the surface color of the titanium material and the base color.
[0047] The titanium material in this embodiment includes a passivation coating and a substrate portion covered by the passivation coating, i.e., the titanium base material. Furthermore, the thicker the passivation coating formed on the surface of the base material, the greater the light interference effect, and the greater the color difference ΔE. * The larger ab is, the greater the color difference ΔE. Therefore, in order to maintain the original metallic color of titanium, the aforementioned color difference ΔE... * ab is below 6.14. This is because if the aforementioned color difference ΔE * If ab is greater than 6.14, then in a visual sensory inspection, the surface color of the titanium material cannot be considered approximately the same as the reference color. The aforementioned color difference ΔE * ab is preferably 5.50 or less, more preferably 5.00 or less. The above color difference ΔE * The smaller ab is, the better the choice, therefore the lower limit is 0.
[0048] It should be noted that the color difference between the titanium material's surface and the reference color is determined through the following steps. First, the L color is measured on the surface of the titanium material. * a * and b * In the measurement, a colorimeter (Konica Minolta CR-400 colorimeter) is used with light source C for measurement. Next, L is calculated by measuring the surface area of the titanium material. * a * and b * L0, respectively, with the reference color * a0 * and b0 * The difference ΔL * , Δa * Δb * Substitute into the following equation (a) to calculate the color difference ΔE. * ab.
[0049]
[0050] 1-2. XPS Measurement
[0051] In this application, by enriching N (nitrogen) directly beneath the passivation coating, the peeling and damage of the passivation coating are suppressed. As a result, lubricity is improved. Here, the passivation coating is typically composed of TiO2 (titanium dioxide). On the other hand, Ti (titanium) generally reacts more readily with O (oxygen) than N. In the case of a dense TiO2 passivation coating, the penetration of N into the titanium substrate is hindered. Therefore, it is difficult to enrich N directly beneath the passivation coating using conventional methods such as annealing. Furthermore, during annealing, when the temperature or atmosphere is set such that Ti reacts more readily with N than O, a golden nitride coating is formed, losing the original metallic color of titanium.
[0052] Therefore, as described below, the manufacturing of the titanium material in this embodiment involves two annealing stages: primary annealing and secondary annealing. In the primary annealing, a certain amount of C is dissolved near the surface. Then, in the secondary annealing, N is enriched by the reduction effect of the dissolved C on the passivation coating. However, if C is excessively dissolved, the reduction effect of C in the secondary annealing becomes too strong, resulting in excessive N enrichment, and consequently, the titanium surface will not achieve the desired color. Therefore, it is effective to dissolve a certain amount of C in the primary annealing to a level that does not become oversaturated. It should be noted that it is effective to form a certain amount of TiC as a compound in a manner that prevents C concentration from becoming oversaturated. That is, the lubricity is improved by utilizing the interaction between N, C, and Ti.
[0053] Therefore, in this embodiment, the titanium material is measured from the surface along the depth direction using X-ray photoelectron spectroscopy (XPS). When the position with the highest nitrogen concentration is set as the peak depth, the nitrogen concentration Np, titanium concentration Tp, and carbon concentration Cp at that peak depth satisfy the following formula (ii).
[0054]
[0055] In equation (ii) above, Np, Tp, and Cp are represented by at (atoms)%.
[0056] Figure 1 This is a graph showing the concentration distribution of titanium material in the depth direction in an example of this embodiment. Figure 1 The concentration distributions of O, Ti, N, and C are shown in the figure. Figure 1As shown, when XPS measurements are performed from the surface with the passivation coating along the titanium substrate direction (hereinafter also referred to as the "depth direction"), the N concentration exhibits a distribution that shows a temporary increase forming a peak, followed by a decrease, with the highest concentration at a location slightly deeper than the surface of the substrate. This highest concentration is Np. Furthermore, the location where the nitrogen concentration is Np is the peak depth, directly below the passivation coating, which is the location of the highest N enrichment. The Ti concentration at this peak depth is Tp, and the C concentration is Cp. By calculating the difference between Tp and Cp and the ratio to Np, the degree to which N is enriched relative to Ti in the substrate can be determined.
[0057] Therefore, the Np / (Tp-Cp) of formula (ii) above is 0.48 or higher. This is because, directly beneath the passivation coating, N, which is used to improve lubricity, is sufficiently enriched, thereby forming TiC, which is effective in improving lubricity. Np / (Tp-Cp) is preferably 0.54 or higher. That is, it is preferable to satisfy formula (iii) below.
[0058]
[0059] On the other hand, in formula (ii) above, Np / (Tp-Cp) is 1.09 or less. If Np / (Tp-Cp) is greater than 1.09 and excessively promotes N enrichment, golden TiN or nitrogen-based compounds (compounds containing N, C, O, etc. and Ti) with a brownish color are formed, and the color difference ΔE * If the range of ab is greater than 6.14, setting Np / (Tp-Cp) to below 1.09 is to minimize the color difference ΔE. * ab is defined as the range of titanium materials used in this embodiment. Additionally, this is because it also helps to suppress the decrease in lubricity. Np / (Tp-Cp) is preferably 0.95 or less. That is, it is preferable to satisfy the following formula (iv).
[0060]
[0061] It should be noted that, as mentioned above, the relationship between Np, Tp, and Cp is important, and therefore there are no particular restrictions on individual values. However, from the viewpoint of enriching N and suppressing damage and peeling of the passivation coating, Np is preferably 10 atomic% or more, more preferably 12 atomic% or more, and even more preferably 14 atomic% or more. On the other hand, if N is excessively enriched, it may not achieve the desired color, so Np is preferably 55 atomic% or less, more preferably 51 atomic% or less, even more preferably 49 atomic% or less, and even more preferably 35 atomic% or less. That is, Np is preferably 10 to 55 atomic%, more preferably 12 to 51 atomic%, more preferably 14 to 49 atomic%, and even more preferably 14 to 35 atomic%.
[0062] Furthermore, the aforementioned TiC does not have a reducing effect, but it is effective in improving lubricity. The value of Cp increases proportionally with the amount of TiC. If Cp is 3 atomic% or more, sufficient TiC is formed; therefore, Cp is preferably 3 atomic% or more, more preferably 10 atomic% or more, more preferably 12 atomic% or more, and even more preferably 14 atomic% or more. On the other hand, if Cp is 26 atomic% or less, excessive enrichment of N can be suppressed; therefore, Cp is preferably 26 atomic% or less, more preferably 24 atomic% or less, and even more preferably 22 atomic% or less. That is, Cp is preferably 3 to 26 atomic%, preferably 10 to 26 atomic%, more preferably 12 to 24 atomic%, and even more preferably 14 to 22 atomic%.
[0063] Considering the balance with the preferred ranges of Np and Cp, Tp is preferably 36 atomic% or more, more preferably 38 atomic% or more, and even more preferably 40 atomic% or more. Furthermore, Tp is preferably 54 atomic% or less, more preferably 52 atomic% or less, and even more preferably 50 atomic% or less. That is, Tp is preferably 36 to 54 atomic%, more preferably 38 to 52 atomic%, and even more preferably 40 to 50 atomic%.
[0064] There is no particular limitation on the peak depth of the highest nitrogen concentration. However, the titanium material of this embodiment is manufactured by a two-stage annealing process. When manufactured using this method, the peak depth is directly below the passivation coating, so its depth is 50 nm or less. More preferably, the depth is 30 nm or less. The lower limit of this depth is greater than 0 nm, and preferably 1 nm or more.
[0065] In the titanium material of this embodiment, the thickness of the passivation coating is not particularly limited as long as the color difference requirement described above is met. For example, it is preferably 20 nm or less, more preferably 15 nm or less, and even more preferably 10 nm or less. It should be noted that the passivation coating is inevitably formed, so its thickness is greater than 0 nm. In addition, if lubricity is taken into consideration, the thickness of the passivation coating is preferably 3 nm or more, and more preferably 5 nm or more.
[0066] It should be noted that the determination of Np, Tp, and Cp can be performed according to the following steps. XPS is used in the determination. For a 1mm diameter area of the test piece taken from titanium material, Ar ion sputtering and elemental concentration measurement are repeatedly performed from the surface to determine the elemental concentration distribution along the depth direction. The concentrations of Ti, O, N, C, Fe, Cu, Sn, Si, Nb, Al, and V are measured at 1nm intervals from the surface to a SiO2 equivalent depth of 1-5nm, and at 5nm intervals in deeper regions closer to the titanium substrate. Based on the measurement results, the position with the highest N concentration is defined as the peak depth, the N concentration at the peak depth is defined as Np, the C concentration at the peak depth is defined as Cp, and the Ti concentration at the peak depth is defined as Tp. It should be noted that when the peak depth is greater than two points, the depth closest to the surface is taken as the peak depth.
[0067] Furthermore, the thickness of the passivation coating is determined by measuring the O concentration along the depth direction of the base material from the surface. Specifically, when the maximum O concentration is set to 100%, the minimum depth at which the O concentration is below 50% is taken as the thickness of the passivation coating.
[0068] 1-3. Types and shapes of titanium materials
[0069] The type of titanium material used in this embodiment is not particularly limited. That is, any titanium material, industrial-grade pure titanium, or titanium alloy is acceptable. It should be noted that industrial-grade pure titanium is specified by JIS, ASTM, etc., and typically has a Ti content of 99% by mass or higher.
[0070] For general industrial-grade pure titanium, examples include JIS 1 to 4 types or ASTM / ASME Grade 1 to 4. Representative impurity elements in industrial-grade pure titanium are C, H, O, N, and Fe. In the aforementioned industrial-grade pure titanium, the content of these elements is as follows: C: less than 0.08% by mass, H: less than 0.015% by mass, O: less than 0.40% by mass, N: less than 0.05% by mass, and Fe: less than 0.50% by mass.
[0071] In addition, titanium alloys typically refer to alloys containing more than 70% by mass of Ti. Examples of titanium alloys include α-type titanium alloys, α+β-type titanium alloys, and β-type titanium alloys. Examples of α-type titanium alloys include high corrosion-resistant alloys (those specified in JIS standards 11-13, 17, 19-22, and ASTM standards Grades 7, 11, 13, 14, 17, 30, and 31, or further titanium alloys containing small amounts of various elements), Ti-0.5Cu, Ti-1Cu, Ti-1Cu-0.5Nb, Ti-1Cu-1Sn-0.35Si-0.25Nb, etc. It should be noted that, for example, Ti-0.5Cu refers to a titanium alloy containing approximately 0.5% by mass of Cu; Ti-1Cu-0.5Nb refers to a titanium alloy containing approximately 1.0% by mass of Cu and approximately 0.5% by mass of Nb. Thus, in the name of titanium alloys, the elements contained and their contents are usually listed after Ti- (see, for example, https: / / www.nipponsteel.com / product / titan / pdf / index02.pdf).
[0072] Examples of α+β type titanium alloys include Ti-3Al-2.5V, Ti-5Al-1Fe, Ti-5Al-2Fe-0.25Si, and Ti-6Al-4V. Examples of β type titanium alloys include Ti-11.5Mo-6Zr-4.5Sn, Ti-3Al-8V-6Cr-4Mo-4Zr, Ti-13V-11Cr-3Al, Ti-15V-3Al-3Cr-3Sn, Ti-20V-4Al-1Sn, and Ti-22V-4Al.
[0073] The shape of the titanium material is not particularly limited. It can be a sheet, a rod, or other shapes. That is, the titanium material in this embodiment includes titanium plates, titanium rods, etc.
[0074] 2. Lubricity
[0075] The titanium material of this embodiment, while satisfying the above-described technical characteristics, can improve lubricity, and when using the liquid lubricant described later, the average coefficient of friction measured on the surface is preferably less than 0.20. Furthermore, even without lubrication, the average coefficient of friction is preferably less than 0.30, and more preferably less than 0.20.
[0076] The average coefficient of friction was determined by performing a pin-disc friction and wear test according to the following steps. In this application, a pin-disc friction and wear tester was used, and the surface of the titanium material was slid by a pin to perform the friction and wear test. When a lubricant was used for the test, the lubricant was Castrol (manufactured by TAIYU CO.,LTD., S-803T) diluted with water to 4 times. In the case of no lubrication, the test was performed without lubricant. The average coefficient of friction was calculated under the conditions of surface pressure of 1 MPa, speed of 0.1 m / min, and sliding distance of 20 mm. In addition, the pin used in the test was made of high carbon chromium bearing steel SUJ2 as specified in Japanese Industrial Standard JIS G4805:2019, with a smooth surface of φ3.5 mm and an arithmetic mean roughness Ra of 0.12 μm.
[0077] 3. Processed goods and finished products
[0078] The titanium material of this embodiment has excellent lubricity, which can suppress mold wear, and therefore can be processed in various ways to be used as a finished product. That is, the finished product is made by processing the above-mentioned titanium material. Examples of processing methods include pressing or shearing. Examples of finished products made of titanium material include porous metal mesh, partitions, bipolar plates, and titanium plates for plate heat exchangers. Furthermore, titanium material and / or finished products made of titanium material can also be used to manufacture products such as plate heat exchangers.
[0079] Even in the processed state, at least a portion of its surface retains the original surface color. That is, in processed articles made from the titanium material of this embodiment, at least a portion of the surface retains its original color (L). * ,a * ,b * ) and the reference color (L0) represented by the following formula (i) * ,a0 * ,b0 * The color difference ΔE * The ab value is below 6.14.
[0080]
[0081] Furthermore, X-ray photoelectron spectroscopy was used to measure the nitrogen concentration along the depth direction from the aforementioned surface. When the position with the highest nitrogen concentration was taken as the peak depth, the nitrogen concentration Np, titanium concentration Tp, and carbon concentration Cp at the peak depth satisfied the following equation (ii). The reasons for these limitations are the same as those for titanium materials, so the explanation is omitted.
[0082]
[0083] In equation (ii) above, Np, Tp, and Cp are represented by at (atoms)%.
[0084] 4. Manufacturing method
[0085] The titanium material of this embodiment can be stably manufactured by, for example, the following manufacturing method.
[0086] 4-1. Hot-rolled
[0087] First, prepare the hot-rolled billet. This billet can be made of industrial-grade pure titanium or titanium alloy; there are no particular restrictions on its type. It should be noted that the hot-rolled billet can be manufactured using conventional methods. For example, a titanium billet ingot can be created by arc melting, followed by hot forging to produce the hot-rolled billet.
[0088] The aforementioned hot-rolled billet is hot-rolled to produce hot-rolled material. There are no particular limitations on the hot-rolling conditions. Adjustments can be made as needed to achieve the desired properties. The resulting hot-rolled material can then be subjected to appropriate heat treatment.
[0089] 4-2. Cold rolling
[0090] Then, the hot-rolled material is cold-rolled to produce a cold-rolled material. During cold rolling, a cold-rolling oil containing carbon (C) is used. In the titanium material of this embodiment, commercially available mineral oil or soluble oil is preferably used as the cold-rolling oil. Considering reactivity, mineral oil is preferred over soluble oil. By using such a cold-rolling oil, a mechanochemical reaction occurs during cold rolling, where the titanium material surface reacts with the C in the cold-rolling oil. As a result, C is enriched in the surface layer. It should be noted that before the first annealing after cold rolling, melting, grinding, etc., are not performed. This is because if melting or grinding is performed after cold rolling, the C-enriched surface layer is removed.
[0091] In addition, cold rolling is usually carried out using a Sendzimir mill. In a Sendzimir mill, titanium is rolled by repeatedly passing it through a pair of work rolls. Here, the passage of titanium through the work rolls is called a pass. Therefore, in cold rolling, multiple passes are typically used to control the target thickness. That is, cold rolling is a multi-pass process.
[0092] Furthermore, in the manufacturing of the titanium material according to this embodiment, the average reduction rate of all passes in cold rolling is not particularly limited, but is preferably in the range of 7% to 20%. This is because if the average reduction rate is 7% or higher, a mechanochemical reaction is more likely to occur. In addition, if the average reduction rate is 20% or lower, it is difficult to produce surface defects.
[0093] It should be noted that the above-mentioned reduction rate can be calculated by the following formula (b).
[0094]
[0095] The symbols in equation (b) above are defined as follows.
[0096] h1 (mm): Thickness of titanium material before each pass
[0097] h2 (mm): Thickness of titanium material after each pass
[0098] 4-3. First annealing
[0099] Next, the obtained cold-rolled material undergoes a first annealing. In this first annealing, the C enriched in the surface layer during cold rolling is stabilized by converting it into a certain amount of C and TiC dissolved in the surface layer. Additionally, recrystallization can be promoted during the first annealing, thereby adjusting the grain diameter. It should be noted that such microstructure control can be achieved through a second annealing process, described later.
[0100] Solid C plays a reducing role in the secondary annealing process described later, which is necessary for N enrichment in order to remove the passivation coating in one step. Although TiC does not exhibit a reducing effect, it improves lubricity by being present directly beneath the passivation coating after secondary annealing. In addition, a certain amount of TiC is formed to achieve the desired amount of solid C.
[0101] Here, the annealing temperature and time in the first annealing are set to a range of Larssen-Müller parameters (LMP) of 8600 or higher, as shown in equation (c). For example, if the values are 550°C, 3 hours or more, 650°C, 20 minutes or more, 750°C, 3.5 minutes or more, 850°C, 20 seconds or more, then the LMP is 8600 or higher. This is because, by ensuring that the annealing temperature and time meet the above range, the reduction reaction of C is less likely to occur excessively in the second annealing, thus reducing the color difference ΔE. * The values of ab and the intermediate terms of equation (ii) are within the expected range.
[0102] It should be noted that there is no particular upper limit to the LMP used to control the annealing temperature and time, but the LMP preferably controls the annealing temperature and time to below 11,000 °C. If the C enriched on the surface becomes thinner due to inward diffusion, this effect cannot be achieved, but this would require an impractically long time, therefore there is no practical upper limit. On the other hand, if the titanium grains become excessively coarse, the formability decreases, so the upper limit of the LMP is preferably below 11,000 °C.
[0103]
[0104] In equation (c) above, Log represents the common logarithm to base 10, and the symbols are defined as follows. It should be noted that unless otherwise specified, Log always represents the common logarithm.
[0105] T: Annealing temperature (°C) during a single annealing process.
[0106] t: Annealing time (h) in one annealing cycle
[0107] In addition, there is no lower limit to the heating rate from cold rolling to the annealing temperature of the first annealing, but from the point of view of LMP and productivity, the heating rate from the annealing temperature of the first annealing is preferably 20°C / s or more.
[0108] The annealing atmosphere during a single annealing process is either a vacuum or an Ar atmosphere. In a vacuum atmosphere, the pressure is preferably less than 0.01 Pa. On the other hand, in an Ar atmosphere, Ar gas with a purity of 5 N or higher is used, preferably with an oxygen concentration of less than 1 vol. ppm and a dew point of less than -50°C. This is because, by using such an annealing atmosphere, excessive growth of the passivation coating on the surface can be suppressed, reducing the color difference ΔE. * ab represents the desired range.
[0109] After holding at the annealing temperature, cool to below 200°C and remove from the furnace. After cooling to 200°C and removing from the furnace, perform a secondary annealing as described later within 7 days. By performing secondary annealing within 7 days, the formation of a dense and thick passivation film can be suppressed, and nitrogen can be sufficiently enriched through secondary annealing.
[0110] A passivation film is temporarily formed after the first annealing, but if this passivation film is dense and thick, it is difficult for N to accumulate during the second annealing. Therefore, in order to avoid the formation of such a passivation film, the conditions for the first annealing are set within the above range.
[0111] 4-4. Secondary annealing
[0112] Next, the cold-rolled material that has undergone one annealing is subjected to a second annealing. The second annealing is a so-called nitriding annealing, in which the dissolved carbon in the first annealing plays a reducing role, the passivation coating is removed in one step, and nitrogen is enriched in the titanium base material. Through this enriched nitrogen, the lubricity is improved.
[0113] Here, the annealing temperature in the secondary annealing is 500~850℃. This is because by setting the annealing temperature above 500℃, N can be sufficiently enriched, and the intermediate term of equation (ii) can be within the desired range. On the other hand, by setting the annealing temperature below 850℃, the color difference ΔE can be reduced. * ab represents the desired range. It should be noted that, after cold rolling, the heating rate to the secondary annealing temperature is preferably 20°C / s or higher. This is because, by maintaining the heating rate within the above range, excessive growth of the passivation coating can be suppressed.
[0114] Similarly, the holding time required after reaching the annealing temperature varies depending on each nitriding temperature, and the annealing time relative to the annealing temperature in secondary annealing is preferably within the range of the following equation (d) experimentally.
[0115]
[0116] In equation (d) above, Log is a common logarithm with base 10, and the symbols are defined as follows.
[0117] T: Annealing temperature (°C) during secondary annealing
[0118] tc: Annealing time (s) in the secondary annealing process.
[0119] Based on the above equation (d), for example, at 550°C for more than 870s, at 650°C for more than 82s, at 750°C for more than 10s, and at 800°C for more than 4s, N can be enriched, and the intermediate term of equation (ii) can be made to be within the desired range.
[0120] Furthermore, the annealing time relative to the above-mentioned annealing time is preferably satisfied by the following equation (e). This is because if the annealing time satisfies the following equation (e), the intermediate term of equation (ii) can be made to be within a more preferred range.
[0121]
[0122] In equation (e) above, Log is a common logarithm with base 10, and the symbols are defined as follows.
[0123] T: Annealing temperature (°C) during secondary annealing
[0124] tc: Annealing time (s) in the second annealing process.
[0125] It should be noted that from a lubrication point of view, there is no upper limit to the annealing time. However, if the annealing time is too long, a passivation coating will grow, resulting in a golden-yellow appearance, which is not preferred. This is because if the annealing time is too long relative to the annealing temperature, the reduction effect of C is lost, leading to the growth of the passivation coating. Therefore, the upper limit of the commonly used logarithm of the annealing time is preferably less than the value on the right side of equation (f), that is, the annealing time preferably satisfies equation (f).
[0126]
[0127] In the above formula (f), Log is a common logarithm with base 10, and the symbols are defined as follows.
[0128] T: Annealing temperature (°C) during secondary annealing
[0129] tc: Annealing time (s) in the secondary annealing process.
[0130] It should be noted that the above equations (d) to (f) were obtained through experiments. Although the details are unknown, they are speculated to be based on the diffusion distance of nitrogen.
[0131] The annealing atmosphere in the secondary annealing is a nitrogen atmosphere. At this time, a nitrogen gas with a purity of 5N or higher is used, preferably with an oxygen concentration of less than 1 vol.ppm and a dew point of less than -50°C. This is because, by using such an annealing atmosphere, excessive growth of the passivation coating on the surface can be suppressed, thus reducing the color difference ΔE. * ab represents the desired range. Furthermore, this is because it allows the intermediate term in equation (ii) to be within the desired range. After secondary annealing, the material is cooled to approximately room temperature (25°C) to obtain the titanium material of this embodiment.
[0132] The titanium material of this embodiment will be described in more detail below through examples, but this embodiment is not limited to these examples.
[0133] Example
[0134] Prepare titanium billets with a thickness of 4 mm and the chemical composition shown in Table 1. These billets are manufactured through hot rolling and other processes. It should be noted that, for simplicity, industrial-grade pure titanium in Table 1 is simply listed as pure titanium.
[0135] [Table 1]
[0136]
[0137] The titanium billet was cold-rolled under the conditions shown in Tables 2 and 4. Commercially available mineral oil or soluble oil was used during cold rolling until the sheet thickness reached 0.5 mm. It should be noted that the cold rolling was performed in multiple passes, and the average reduction rate was also calculated. Then, a first annealing and a second annealing were performed to obtain the titanium material. The annealing atmosphere listed in the tables as "0.001 Pa" or "0.01 Pa" refers to the gas pressure inside the annealing furnace.
[0138] It should be noted that, as shown in Tables 2-5, in some examples, solution cutting or grinding is performed before and after the first annealing. In solution cutting, fluorinated nitric acid is used to reduce the plate thickness by more than 10 μm on one side (more than 20 μm total on both sides). Additionally, in some examples of grinding, the abrasive paper grit is switched from coarse to fine grit in the order of P150, P600, and P1000, and finally finished with P2000 to reduce the plate thickness by a total of 100 μm. It should be noted that the final finishing grit is recorded in the tables. The grinding direction changes by 90° at the time of grit switching. In mirror polishing, after grinding with P1000 abrasive paper, a mirror finish is achieved by polishing with colloidal silica. Furthermore, after the first annealing, the plate is cooled to below 200°C. The temperature at which it is removed from the annealing furnace is recorded in the table as the removal temperature. Additionally, the nitrogen used in the second annealing has a purity of 5N or higher. Furthermore, the heating rate for both the first and second annealing is 30°C / s. It should be noted that the minimum and maximum values of tc in the table are calculated based on equations (d) and (f).
[0139] In Example No. 30 of this invention, after cutting a blank with a diameter of 108 mm from the obtained plate-shaped titanium material, a deep drawing process is performed using a punch with a diameter of 40 mm to make the drawing depth 20 mm, thereby producing a finished product.
[0140] [Table 2]
[0141]
[0142] [Table 3]
[0143]
[0144] [Table 4]
[0145]
[0146] [Table 5]
[0147]
[0148] The color difference ΔE of the obtained titanium material was measured according to the following steps. * ab, the concentrations of each element (Np, Cp, and Tp) and the average coefficient of friction. Regarding Example No. 30 of this invention, measurements were performed on the flange portion of the processed article.
[0149] (color difference ΔE) * ab)
[0150] First, L is measured on the surface of the flange portion of the titanium material or the processed product. * a * and b * In the measurement, a colorimeter (Konica Minolta CR-400 colorimeter) was used with light source C. Next, L, obtained by measuring the surface area of the flange portion of the titanium material or machined workpiece, was calculated. * a * and b * L0, respectively, with the reference color * a0 * and b0 * The difference ΔL * , Δa * Δb * Substitute into the following equation (a) to calculate the color difference ΔE. * ab.
[0151]
[0152] (Concentrations of each element (Np, Cp, and Tp))
[0153] Using a JEOL XPS (model: JPS-9200), a 1 mm diameter area of a test piece taken from the flange portion of titanium or a machined product was repeatedly sputtered from the surface using Ar ions, and the elemental concentration distribution in the depth direction was determined. For the measurement, acetone (ultrasonic) degreasing was performed as a pretreatment. A line connecting the maximum and minimum values of the binding energy (BE) within the range specified below was used as the background. The elemental concentration was determined based on the BE after background removal. The background treatment was performed using JEOL's SPECSURF software.
[0154] Regarding the BE range, after correction to a peak value of 285 eV for C Graphite in the surface qualitative determination, the range was set to 275–300 eV for C, 445–470 eV for Ti, 520–540 eV for O, 385–410 eV for N, and any value for other elements that encompasses all peaks within a BE width of 25 eV. The concentrations of Ti, O, N, C, Fe, Cu, Sn, Si, Nb, Al, and V were determined at 1 nm intervals from the surface to a SiO2 equivalent depth of 1–5 nm, and at 5 nm intervals in deeper regions than the titanium substrate side.
[0155] Based on the measurement results, the position with the highest N concentration was designated as the peak depth, the N concentration at the peak depth was designated as Np, the C concentration at the peak depth was designated as Cp, and the Ti concentration at the peak depth was designated as Tp. It should be noted that when the peak depth is greater than two points, the depth at the outermost surface is used as the peak depth. Furthermore, the passivation coating thickness was calculated using the O concentration at the outermost surface and the O concentration at each depth from the surface. Specifically, when the O concentration at the outermost surface was set to 100%, the minimum depth where the O concentration was 50% or less was recorded as the passivation coating thickness in the table.
[0156] (Average coefficient of friction)
[0157] Friction and wear tests were conducted using a pin-disc friction and wear tester, where pins were used to slide the surface of the flange portion of titanium materials or machined parts. Measurements were performed under both conditions: with and without liquid lubricant. When lubricant was used, it was Castrol (S-803T) diluted 4 times with water. In the unlubricated condition, the test was conducted without lubricant. The average coefficient of friction was calculated under a surface pressure of 1 MPa, a speed of 0.1 m / min, and a sliding distance of 20 mm. The pins used in the tests were made of high-carbon chromium bearing steel SUJ2 as specified in Japanese Industrial Standard JIS G4805:2019, with a smooth surface of φ3.5 mm and an arithmetic mean roughness Ra of 0.12 μm. The results are summarized in the table below.
[0158] [Table 6]
[0159]
[0160] [Table 7]
[0161]
[0162] Examples No. 1-5, 7, 12, 13, 15, 17, 20, 22, and 24-30 of this invention also satisfy the color difference ΔE. * ab has the characteristics and also satisfies equation (ii), therefore it also has good lubricity.
[0163] In Examples No. 6, 8-11 of this invention, because the conditions for the first annealing were slightly worse than those in the examples described above, the reduction reaction of C occurred slightly excessively. Therefore, the intermediate term value of Formula (ii) is 0.96 or higher, resulting in slightly worse lubricity compared to the examples described above. Similarly, in Examples No. 14, 16, 18, 19, 21, and 23 of this invention, because the conditions for the second annealing were slightly worse, the intermediate term value of Formula (ii) is less than 0.54, resulting in slightly worse lubricity compared to the examples No. 1-5, etc., of this invention.
[0164] Comparative Examples No. 1-4, due to surface removal before the first annealing, resulted in insufficient C enrichment on the surface layer and inadequate reduction during the second annealing. Consequently, during the second annealing, oxygen in the nitrogen preferentially reacted, forming a thick passivation coating, ΔE * ab is greater than 6.14. In comparative examples No. 5-7, because the annealing atmosphere during the first annealing was outside the preferred range, a thick passivation film was formed on the surface, ΔE * ab is greater than 6.14.
[0165] In Comparative Examples No. 8-15, because the primary annealing temperature or holding time was outside the preferred range, the reduction reaction of C occurred excessively, the intermediate term of Formula (ii) was greater than 1.09, and compounds of Ti, C, O and / or N were excessively formed, thus ΔE * ab is greater than 6.14. In Comparative Example No. 16, because the removal temperature after the first annealing was too high, a dense passivation film was formed. As a result, the reduction effect brought about by C could not be fully obtained in the second annealing. Therefore, the value of the intermediate term in Equation (ii) is less than 0.48, and the lubricity is reduced.
[0166] Comparative examples No. 17 and 18, due to the subsequent solution cutting or coarse-grained grinding after the first annealing, had a lower surface carbon concentration, resulting in insufficient reduction during the second annealing. Consequently, oxygen in the nitrogen preferentially reacted, forming a thick passivation coating, thus ΔE * ab is greater than 6.14.
[0167] In Comparative Examples No. 19-21, because the period between the first annealing and cooling and the second annealing exceeded 7 days, the passivation film after the first annealing was dense. As a result, the reduction effect brought by C could not be fully obtained in the second annealing. Therefore, the value of the intermediate term in Equation (ii) was less than 0.48, and the lubricity was reduced. In Comparative Examples No. 22 and 23, because the annealing atmosphere of the second annealing was outside the range of preferred conditions, a thick passivation film was formed on the surface, ΔE * ab is greater than 6.14.
[0168] In Comparative Examples No. 24-26 and 28-31, because the secondary annealing temperature or holding time was outside the preferred range, the enrichment of N was insufficient, the intermediate term of Equation (ii) was less than 0.48, and the lubricity was reduced. In Comparative Example No. 27, because the holding time of the secondary annealing was too long, a thick passivation film was formed on the surface, ΔE * ab is greater than 6.14. In comparative examples No. 32 and 33, because no annealing was performed, the reduction reaction of C occurred excessively, resulting in the excessive formation of compounds of Ti, C, O, and N. Consequently, ΔE * ab is greater than 6.14. In comparative example No.34, because no secondary annealing was performed, N was not enriched, the intermediate term value of equation (ii) is less than 0.48, and the lubricity is reduced.
Claims
1. A titanium material, wherein, In L * a * b * In the coloring system, the surface color (L) of the titanium material * ,a * ,b * ) and the reference color (L0) represented by the following formula (i) * ,a0 * ,b0 * The color difference ΔE * AB is below 6.
14. Measurements were performed along the depth direction from the surface using X-ray photoelectron spectroscopy. When the position of maximum nitrogen concentration was taken as the peak depth, the nitrogen concentration Np, titanium concentration Tp, and carbon concentration Cp at that peak depth satisfied the following equation (ii). In formula (ii), Np, Tp, and Cp are represented by atomic percentages.
2. The titanium material according to claim 1, further satisfying the following formula (iii), 。 3. The titanium material according to claim 1 or 2, further satisfying the following formula (iv), 。 4. A processed article, which is a processed article of titanium material, wherein, In L * a * b * In the coloring system, the color (L) of at least a portion of the surface of the processed article * ,a * ,b * ) and the reference color (L0) represented by the following formula (i) * ,a0 * ,b0 * The color difference ΔE * AB is below 6.
14. Measurements were performed along the depth direction from the surface using X-ray photoelectron spectroscopy. When the position of maximum nitrogen concentration was taken as the peak depth, the nitrogen concentration Np, titanium concentration Tp, and carbon concentration Cp at that peak depth satisfied the following equation (ii). In formula (ii), Np, Tp, and Cp are represented by atomic percentages.
5. An article comprising the titanium material according to any one of claims 1 to 3 and / or the processed article according to claim 4.
Citation Information
Patent Citations
Titanium material having surface ruggedness and its production method
JP2005298930A
Titanium plate excellent in lubricity and method for manufacturing the same
JP2020183551A